Pendirian Usaha Produksi Kriya Batik Tulis Dan Cap - Mulyanto Mulyanto (Mudra Jurnal Seni Budaya, 2022)
Batik has become everyday clothing for the people of Indonesia, many batik businesses have sprung up in several regions in Indonesia. The purpose of this study is to describe the minimum standards of aspects needed to establish a batik craft business. These aspects include capital funds, materials, equipment, employees, human resource management, production management, financial management, and marketing management. This qualitative descriptive research was conducted in several batik craft businesses on the island of Java. Twenty key informants consisted of 10 batik entrepreneurs, 3 motive designers, 3 batik makers, 1 stamper, and 3 color workers. The research data was collected through interview techniques, focus group discussion, document observation and study, then analyzed using interactive models. To establish a batik business with an initial production process for one month, a fund of Rp.37,350,000.00 is needed, 5 batik makers, 1 color dealer, an area of 100m2 and a building of 64m2. To establish a combination of stamp and writing batik business with an initial production process for one month, funds amounting to Rp 113,900,000.00, 4 employees, land 100m2 and building 69m2 are needed. The establishment of a batik business is estimated to be the main point of return for 7 months.